2013
DOI: 10.1155/2013/627384
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and the Lung: Connecting Asthma and Metabolic Syndrome

Abstract: Obesity, metabolic syndrome, and asthma are all rapidly increasing globally. Substantial emerging evidence suggests that these three conditions are epidemiologically and mechanistically linked. Since the link between obesity and asthma appears to extend beyond mechanical pulmonary disadvantage, molecular understanding is necessary. Insulin resistance is a strong, independent risk factor for asthma development, but it is unknown whether a direct effect of insulin on the lung is involved. This review summarizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 90 publications
(84 reference statements)
3
60
1
6
Order By: Relevance
“…Furthermore, we found that insulin can directly induce molecular signaling events associated with airway smooth muscle proliferation, collagen deposition, and epithelial mesenchymal transition (EMT). A link between insulin resistance, consequent hyperinsulinemia, and asthma is well supported by previous evidence (2,34,38). Increased fasting insulin levels are previously reported in humans with features of insulin resistance (12,27).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Furthermore, we found that insulin can directly induce molecular signaling events associated with airway smooth muscle proliferation, collagen deposition, and epithelial mesenchymal transition (EMT). A link between insulin resistance, consequent hyperinsulinemia, and asthma is well supported by previous evidence (2,34,38). Increased fasting insulin levels are previously reported in humans with features of insulin resistance (12,27).…”
Section: Discussionsupporting
confidence: 57%
“…Hence, it is not clear whether insulin resistance, with consequent hyperinsulinemia, is a dependent surrogate marker or whether it independently contributes to increased risk of respiratory disease. Furthermore, although there is sufficient basis to hypothesize that hyperinsulinemia is mechanistically related to increased risk of asthma or other lung diseases, there are only limited data to support this idea, with insulin showing potentiation of airway smooth muscle (ASM) contraction in animals (15,32), which remains to be confirmed in human airways (34). Indeed, the mechanisms by which insulin influences airway elements to produce structural and functional changes in the asthmatic airway are also not known.…”
mentioning
confidence: 99%
“…1). Air pollution exposure has been linked to both asthma and obesity (Eze et al, 2015b;Jacquemin et al, 2015;Jerrett et al, 2014), and studies have linked asthma to obesity and insulin resistance (Husemoen et al, 2008;Sanchez Jimenez et al, 2014;Singh et al, 2013). While there is a consensus that obesity-related systemic inflammation likely contributes to the asthma etiology, epidemiological evidence on the relationship between asthma and diabetes is limited and conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…Это может приводить к ухудшению функциональных показателей лег-ких [9,17], особенно при сочетании БА и СД2.…”
Section: Discussionunclassified
“…Функционирование провоспалительных ци-токинов, таких как TNFα и IL-1β, координиру-ет, как предполагается, IL-6, показана его роль в развитии СД2 [17,20].…”
Section: цитокиновый спектр при сочетании ба C сд Ii Cytokines In Brounclassified